Do You Like Listening To Song? : Students’ Perspective On Vocabulary Learning Through English Song - Hasaniyah, Nikmatul; Suryanto, Bradiansyah Tri (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to examine students' perspectives on the use of English songs as a medium for vocabulary learning at MAN Negeri 1 Probolinggo. In the context of English language learning, vocabulary mastery plays an important role as the foundation for effective language proficiency. However, the lack of interest among students in learning English is often caused by unengaging teaching methods. Songs as a learning medium are presented to create a fun and interactive learning atmosphere. Through a qualitative approach, this research collects data from interviews, observations, and documentation of students participating in music-based English extracurricular activities. The research results show that songs can enhance learning motivation, facilitate vocabulary mastery, and improve listening and pronunciation skills. Students' positive perception of this method encourages increased engagement and understanding in English language learning. Therefore, the integration of songs in vocabulary learning can be an effective strategy to overcome affective barriers and improve student learning outcomes. This study recommends the implementation of more interactive and contextual learning methods, as well as the optimization of using songs as a medium for English language learning.